2010
DOI: 10.1088/0004-637x/723/2/1549
|View full text |Cite
|
Sign up to set email alerts
|

GALEXOBSERVATIONS OF DIFFUSE ULTRAVIOLET EMISSION FROM DRACO

Abstract: We have studied small scale (2 ′ ) spatial variation of the diffuse UV radiation using a set of 11 GALEX deep observations in the constellation of Draco. We find a good correlation between the observed UV background and the IR 100 µm flux, indicating that the dominant contributor of the diffuse background in the field is the scattered starlight from the interstellar dust grains. We also find strong evidence of additional emission in the FUV band which is absent in the NUV band. This is most likely due to Lyman… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 35 publications
3
25
0
Order By: Relevance
“…A comparative review of past work can be found in Gordon (2004). Recently, GALEX observations provided diffuse UV background images with high spatial resolution, which have been used for the determination of the albedo and the g-factor in both the FUV (1350-1750 Å) and NUV (1750-2850 Å) bands (Sujatha et al 2009(Sujatha et al , 2010. Most of these studies showed that the interstellar grain causes a strong forward scattering in the FUV, with a moderate albedo, which is in good agreement with theoretical predictions.…”
Section: Introductionsupporting
confidence: 60%
“…A comparative review of past work can be found in Gordon (2004). Recently, GALEX observations provided diffuse UV background images with high spatial resolution, which have been used for the determination of the albedo and the g-factor in both the FUV (1350-1750 Å) and NUV (1750-2850 Å) bands (Sujatha et al 2009(Sujatha et al , 2010. Most of these studies showed that the interstellar grain causes a strong forward scattering in the FUV, with a moderate albedo, which is in good agreement with theoretical predictions.…”
Section: Introductionsupporting
confidence: 60%
“…4. It is interesting to note that this curve follows exactly the same curve of Sujatha et al (2010) and Murthy et al (2001) even though the UV and IR values are totally different. The strong correlation (r = 0.75) between emissions in the FUV and NUV channels ( Fig.…”
Section: Resultssupporting
confidence: 78%
“…UV/IR intensity ratio strongly depends on the optical depth and local effects such as the variation of stellar radiation field in the region (Sujatha et al 2010). From Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Our data point to bluer colours for brighter surface brightnesses. Sujatha et al (2010) find such an increase in the FUV/NUV ratio that they interpreted as a sign of fluorescent emission of molecular hydrogen. In our data, however, we cannot rule out a detection issue, as can be seen from Fig.…”
Section: Ultraviolet Cirrus Detectionmentioning
confidence: 89%
“…With the GALEX telescope and its Allsky Imaging Survey (AIS), extensive studies of the diffuse FUV emission became possible (e.g. Sujatha et al 2010;Hamden et al 2013;Murthy 2014).…”
Section: Introductionmentioning
confidence: 99%